Value orientations of youth and the formation of cultural memory in the region (On the example of the Chechen republic) - Uvaisovna, Kurbanova Lidiya; Nikolaevich, Gunya Aleksey; Sultanovna, Abdulaeva Elita (Edelweiss Applied Science and Technology, 2024)
The article analyzes the characteristics of the Chechen youth, their value attitudes and roles in the formation of cultural memory. The methodological framework covers theoretical and methodological areas of research of two social phenomena that are important signs of the changing world at the beginning of this millennium: cultural memory and the attitude of the younger generation towards it. The analysis of these phenomena is studied on the example of a specific region as a social space at a certain stage of socio-public transformation, where the foundations of traditional society with the prevalence of vertical connections continue to play an important role. At the same time, young people have a special place in the perception and transformation of values, experiencing at the same time a great influence of globalization and information technologies. The empirical basis of the study was socio-demographic data on the Chechen Republic, quantitative and qualitative methods of surveying the youth of the republic: an online survey was conducted among students (N = 92) aged 19-24 years and in-depth interviews among young people (N = 21), whose average age was 30 years. Additional materials were data from the database of surveys and focus groups collected in recent years. The results of the study showed that the transformation of cultural memory in the region is influenced by both structural factors, primarily demographic, migration dynamics, socio-economic living conditions of the population, etc., and cultural and institutional factors that determine the value attitudes of various segments of the population, the discourses prevailing in the society, attitudes to history, politics, etc. The value landmarks of young people play an important role in the formation of the cultural memory of the Chechen society and act as means of stabilizing and renewing the society. A key feature of the Chechen society is a respect towards elders. The succession of values is under threat of breaking intergenerational ties and subject to an unprecedented information aggression. The issues of an objective attitude to history, developing a position on the modernization of the society are acute.